Asymptotic Expansions of the Cubic Spline Collocation Solution for Second-Order Ordinary Differential Equations (Journal of Computational Mathematics, 1988)
In this paper, we consider the following problem $$\begin{cases}u''(x)=f(x,u(x),u'(x)), a\leq x\leq b,\\u(a)=u(b)=0,\end{cases}$$ and obtain the theorem.